2023
DOI: 10.1186/s12864-023-09703-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the Bactrian camel (Camelus bactrianus) reveals candidate genes affecting milk production traits

Huaibing Yao,
Zhihua Dou,
Zhongkai Zhao
et al.

Abstract: Background Milk production traits are complex traits with vital economic importance in the camel industry. However, the genetic mechanisms regulating milk production traits in camels remain poorly understood. Therefore, we aimed to identify candidate genes and metabolic pathways that affect milk production traits in Bactrian camels. Methods We classified camels (fourth parity) as low- or high-yield, examined pregnant camels using B-mode ultrasonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Proper nutrition, access to clean water, and regular veterinary care are essential for maintaining the health of camels and ensuring optimal milk production and quality [8]. Recent research has focused on the genomics of Bactrian camels and the candidate genes related to milk production traits were revealed by transcriptome analysis [9]. A total of 1185 genes related to milk traits, including milk yield, milk protein, milk fat, and milk lactose, were identified [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper nutrition, access to clean water, and regular veterinary care are essential for maintaining the health of camels and ensuring optimal milk production and quality [8]. Recent research has focused on the genomics of Bactrian camels and the candidate genes related to milk production traits were revealed by transcriptome analysis [9]. A total of 1185 genes related to milk traits, including milk yield, milk protein, milk fat, and milk lactose, were identified [10].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1185 genes related to milk traits, including milk yield, milk protein, milk fat, and milk lactose, were identified [10]. Twenty-seven candidate genes and 16 core signaling pathways were connected with maternal parturition, estrogen control, lactation initiation, and milk production features [9]. It was shown that milking camels twice a day can result in higher milk yield and better milk quality compared to milking once a day [11].…”
Section: Introductionmentioning
confidence: 99%
“…Camels play an important role in the grassland animal husbandry of this region, holding a crucial position in the frontier animal husbandry and the ethnic characteristic industries of Mongolian and Kazak in the frontier pastoral areas ( 6 ). The camel breeding industry has transitioned from nomadic to intensive breeding, providing humans with milk, meat, camel hair, and other products, thereby increasing the economic income of herdsmen ( 8 ). While there have been limited global studies on Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%